Experimentation, validation, and uncertainty analysis for engineers - Coleman, Hugh W.; Steele, W. Glenn (John Wiley & Sons, Inc., 2018)
Experimentation, Validation, and Uncertainty Analysis for Engineers, Fourth Edition is an ideal text and guide for researchers, engineers, and graduate and senior undergraduate students in engineering and science disciplines. Knowledge of the material in this Fourth Edition is a must for those involved in executing or managing experimental programs or validating models and simulations. Guides readers through all aspects of experimentation, validation, and uncertainty analysis.